Data-Parallel String-Manipulating Programs - Veanes, Margus; Molnar, David; Mytkowicz, Todd; Livshits, Ben (2012)
Applications ranging from malware detection to graphics to Web security sanitization depend on string transformations, but writing such transformations is a challenge. Making these transformations run in parallel on a cluster of machines or special hardware, as often required for scalability, is an even greater challenge. We answer this challenge with fast, parallel string manipulating code compiled from BEK, a domain-specific language for writing complex string manipulation routines. First, our new compilation pipeline maps a BEK program to an intermediate format consisting of symbolic transducers, which extend classical transducers with symbolic predicates and symbolic assignments. We present a novel algorithm that we call exploration which performs a symbolic partial evaluation of these transducers to obtain simplified, stateless versions of the original program. These simplified versions can be lifted back to BEK, and from there compiled to C#, C, or JavaScript. Next, we show how the resulting transducers, post-exploration, fit into a recent advance in data-parallel compilation of finite state machines. Finally, we describe a concrete implementation built on the Windows High Performance Computing framework in a cluster. We have implemented our code generation pipeline for BEK code corresponding to several real string manipulating functions, such as security sanitizers for Web applications. We use an automatic testing approach to compare our generated code to the original C# implementations and found no semantic deviations. Our generated C# code out-performs handwritten code by a factor of up to 3 and we generate code in C that is a factor of 5 faster. For a cluster with 32 nodes, we see speedups of 13.7 times compared to sequential C# code for an HTML sanitizer over 32GB of data.